Multi-physics analysis of permanent magnet tubular linear motors under severe volumetric and thermal constraints - Li, Fang; Ye, Pei-qing; Zhang, Hui (Journal of Central South University, 2016)
Permanent magnet tubular linear motors (TLMs) arranged in multiple rows and multiple columns used for a radiotherapy machine were studied. Due to severe volumetric and thermal constraints, the TLMs were at high risk of overheating. To predict the performance of the TLMs accurately, a multi-physics analysis approach was proposed. Specifically, it considered the coupling effects amongst the electromagnetic and the thermal models of the TLMs, as well as the fluid model of the surrounding air. To reduce computation cost, both the electromagnetic and the thermal models were based on lumped-parameter methods. Only a minimum set of numerical computation (computational fluid dynamics, CFD) was performed to model the complex fluid behavior. With the proposed approach, both steady state and transient state temperature distributions, thermal rating and permissible load can be predicted. The validity of this approach is verified through the experiment.